Naturel kiss online shopping (NKOS) - Muhammad Amrun Aniq, Mohamed Saidi (2019)
Naturel Kiss is a well-established beauty products company which has received numerous accolades locally and internationally. According to the founder, Naturel Kiss' objectives are to offer Malaysian women with skincare and cosmetic products that are safer, non-toxic, and based on natural local and imported ingredients as best as possible. These products can be purchased via distributors and agents throughout Peninsular Malaysia, Sabah and Sarawak. In addition, these products can also be purchased online through the company’s official website. However, Naturel Kiss is lacking of a mobile application platform that allows the customers to purchase the products at anytime, anywhere with the help of internet. Therefore, Naturel Kiss Online Shopping (NKOS) mobile application is developed to improve the efficiency of Naturel Kiss e-commerce system which later having both webbased and mobile-based online shopping platforms. Naturel Kiss Online Shopping (NKOS) mobile application is developed to facilitate the sale and purchase of users at the tips of their fingers. The objectives of this project are to design a beauty product online shopping mobile application, to develop a prototype for the Naturel Kiss Online Shopping (NKOS) system and to validate the Naturel Kiss Online Shopping (NKOS) prototype as a mobile-based system. This project is developed using the Android Studio software, laptop and Java programming language by using the methodology of Rapid Application Development (RAD). There are four phases in RAD model, which are Requirements Planning, User Design, Construction and Cutover. After developing the system, client will be involved in the User Acceptance Test (UAT) to ensure that the system is functioning according to the requirements without any bugs or errors. The User Acceptance Test (UAT) will prove that the system has fulfilled its objectives and able to solve the problem encountered previously. Hence, as a result from the development, a mobile-based online shopping application is developed and all of the features are functioning properly according to the requirements.